2022
DOI: 10.1111/iju.15134
|View full text |Cite
|
Sign up to set email alerts
|

Impact of functional impairment and cognitive status on perioperative outcomes and costs after radical cystectomy: The role of Barthel Index

Abstract: Objectives To investigate the association between Barthel Index (BI), which measures level of patients independence during daily living activities (ADL), and perioperative outcomes in a large cohort of consecutive bladder cancer (BCa) patients, who underwent radical cystectomy (RC) at a tertiary referral center. Methods We retrospectively evaluated data from clinically nonmetastatic BCa patients treated with RC between 2015 and 2022. For each patient, BI was assessed preoperatively. According to BI score, pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Fourth, we were unable to examine functional and cognitive assessments of the older adults in their activities of daily living within this study. It has been reported that the Barthel index is strongly correlated with perioperative outcomes 27 . However, the absence of such information in the collected data prevented us from investigating its impact.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Fourth, we were unable to examine functional and cognitive assessments of the older adults in their activities of daily living within this study. It has been reported that the Barthel index is strongly correlated with perioperative outcomes 27 . However, the absence of such information in the collected data prevented us from investigating its impact.…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that the Barthel index is strongly correlated with perioperative outcomes. 27 However, the absence of such information in the collected data prevented us from investigating its impact. Finally, the sample size was small.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, multimodal scales are needed to attempt a more comprehensive definition of patient's health status. 1 Radical cystectomy (RC) is indeed a complex surgery associated with high rate of complications. 2 The clinical adoption of standardized comorbidity indexes provides a rational background for a personalized medicine.…”
Section: Editorial Commentmentioning
confidence: 99%
“…As a result, surgeons will face up always more on elderly and frail patients. Therefore, multimodal scales are needed to attempt a more comprehensive definition of patient's health status 1 . Radical cystectomy (RC) is indeed a complex surgery associated with high rate of complications 2 .…”
mentioning
confidence: 99%